Biosafety assessment of Listeria monocytogenes in vegetarian burger patties in Malaysia - Wong, Woan Chwen; Pui, Chai Fung; Chai, Lay Ching; Lee, Hai Yen; Mohamad Ghazali, Farinazleen; Tang, John Yew Huat; Ponniah, Jeyaletchumi; Tuan Chilek, Tuan Zainazor; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
The aim of this study was to examine vegetarian burger patties manufactured by two producers in Malaysia for the presence of Listeria monocytogenes. Brand A was produced by an established food manufacturer while Brand B was produced by a small-scaled food producer. A total of 108 samples of vegetarian burger patties produced by both manufacturers were sampled from retail market and were analyzed by combined MPN-PCR and MPN plating method. Of all the samples tested, ten (9.3%) were found to be contaminated with L. monocytogenes. The L. monocytogenes contamination level in vegetarian burger patties manufactured by producer A (20.9% of the samples were contaminated with 3-1100 MPN/g of L. monocytogenes) was significantly higher (P<0.05) than vegetarian burger patties manufactured by producer B (1.5% of the samples harbored 9.2 MPN/g of L. monocytogenes). Based on the detection and isolation rate obtained with MPN-PCR and MPN-plating, the recovery rate of the L. monocytogenes was estimated to be only 40.0% by MPN-plating approach.